Assessment of Methylglyoxal and Soluble Receptor Advanced Glycation End-Products (sRAGEs) in Pre-Diabetic Patients - F. Hussien, Weaam; A. R. Al-Wasiti, Estabraq; Sh. Khudair, Mahood (Al-Nahrain Journal of Science, 2026)
Prediabetes is a condition between normal glucose levels and increased levels of type 2 diabetes, and it is connected with a high risk of developing diabetes. Methylglyoxal is a highly reactive α-dicarbonyl compound endogenously generated naturally as a byproduct during the glycolytic pathway and is considered the precursor of an advanced glycation end product. sRAGE acting as decoy receptors help reduce inflammation, oxidative stress, and vascular complications. This study aims to measure methylglyoxal as the precursor of an AGE and its receptor in prediabetic as a biomarker for metabolic dysfunction. This study involved 80 participants, including 40 prediabetic patients and 40 healthy controls diagnosed in Al-Imamin Alkadmeen City Hospital, Baghdad, Iraq. Basic data from clinical examination and laboratory were collected for all participants. The serum methylglyoxal was measured by high-performance liquid chromatography, and soluble receptor, while  advanced glycation end-products were measured by using an ELISA technique’s kit. Additional parameters were also measured, such as fasting blood glucose, HbA1c, insulin, HOMA-IR, and lipid profile. Subsequently, in prediabetic patients, methylglyoxal and sRAGE levels are significantly elevated compared to healthy controls. Moreover, FBS, HbA1c, insulin, and HOMA-IR are significantly higher in prediabetic patients (p < 0.001). Based on the findings of this research, methylglyoxal and sRAGE may serve as potential biomarkers for prediabetic patients.